Inter‐Fullerene Electronic Coupling Controls the Efficiency of Photoinduced Charge Generation in Organic Bulk Heterojunctions. Issue 24 (26th September 2016) - Larson, Bryon W.; Reid, Obadiah G.; Coffey, David C.; Avdoshenko, Stanislav M.; Popov, Alexey A.; Boltalina, Olga V.; Strauss, Steven H.; Kopidakis, Nikos; Rumbles, Garry
Abstract : Photoinduced charge generation (PCG) dynamics are notoriously difficult to correlate with specific molecular properties in device relevant polymer:fullerene organic photovoltaic blend films due to the highly complex nature of the solid state blend morphology. Here, this study uses six judiciously selected trifluoromethylfullerenes blended with the prototypical polymer poly(3‐hexylthiophene) and measure the PCG dynamics in 50 fs–500 ns time scales with time‐resolved microwave conductivity and femtosecond transient absorption spectroscopy. The isomeric purity and thorough chemical characterization of the fullerenes used in this study allow for a detailed correlation between molecular properties, driving force, local intermolecular electronic coupling and, ultimately, the efficiency of PCG yield. The findings show that the molecular design of the fullerene not only determines inter‐fullerene electronic coupling, but also influences the decay dynamics of free holes in the donor phase even when the polymer microstructure remains unchanged. Abstract : The generation efficiency of long‐lived photoinduced charges in polymer: fullerene bulk heterojunctions increases dramatically as the strength of intermolecular electronic coupling in the fullerene phase improves. Ultrafast geminate recombination is suppressed when electron delocalization within fullerene clusters is strong, while the opposite is observed when delocalization within the cluster is poor.